2006
DOI: 10.1542/peds.2005-0582
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity and Overweight Status in Young School Children: Results From the Early Childhood Longitudinal Study

Abstract: There are strong arguments for reducing food insecurity among households with young children. This research suggests that these arguments would be based on reasons other than a potential link to obesity. Low activity levels and excessive television watching, however, were strongly related to overweight status, a finding that supports continued efforts to intervene in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
140
3
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(155 citation statements)
references
References 26 publications
7
140
3
5
Order By: Relevance
“…1 Food security is most commonly measured in Canada using the 18-item Household Food Security Survey Model (HFSSM), 2 which is based upon the United States Department of Agriculture 18-item Food Security Module. 3 The Canadian Community Health Survey (CCHS), which tracks food security in Canada, reported that, in 2012, 8.2% of households in Canada were food insecure, with 4.9% of children experiencing moderate or severe food insecurity; the rate of food insecurity increased to 10.8% for households with children under six years of age. 4 The most recent prevalence of food insecurity reported, also using data from the CCHS, was 12.0% in 2014 in participating provinces and territories.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Food security is most commonly measured in Canada using the 18-item Household Food Security Survey Model (HFSSM), 2 which is based upon the United States Department of Agriculture 18-item Food Security Module. 3 The Canadian Community Health Survey (CCHS), which tracks food security in Canada, reported that, in 2012, 8.2% of households in Canada were food insecure, with 4.9% of children experiencing moderate or severe food insecurity; the rate of food insecurity increased to 10.8% for households with children under six years of age. 4 The most recent prevalence of food insecurity reported, also using data from the CCHS, was 12.0% in 2014 in participating provinces and territories.…”
mentioning
confidence: 99%
“…5 Household food insecurity has been associated with multiple nutritional risk factors that may be associated with obesity in toddlers, including lower fruit and vegetable intake 6,7 and higher sugar-sweetened beverage intake, 7 as well as lower levels of physical activity and higher screen time in young children. 8 Poverty has…”
mentioning
confidence: 99%
“…4,5 In children, many studies have demonstrated increased risk of obesity, [6][7][8][9][10][11][12][13] although the results have been mixed. 4,5,[14][15][16][17][18][19] Less research has explored potential pathways through which household food insecurity is related to child weight, especially in families with young infants. Given that Hispanic infants are more likely to be overweight than infants of other ethnicities 20 and to live in foodinsecure households, 2 it is particularly important to understand these potential pathways in this high-risk group.…”
mentioning
confidence: 99%
“…This has been generally observed in developing countries. However, while some authors 29,30 have made similar findings, others have found a higher likelihood of childhood overweight/obesity in poor families, more consistently seen in developed countries 31 , but also observed in Brazil 24,26 .…”
Section: Discussionmentioning
confidence: 75%